2020
DOI: 10.1111/ijfs.14939
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rice bran on physicochemical, textural and glycaemic properties of ready‐to‐eat extruded corn snacks

Abstract: In this work, corn extruded snack products were enriched with rice bran (RB) at 10% and 15%. A co-rotating twin-screw extruder was used with a feed moisture content of 16 g 100 g À1 , a screw speed of 240 r.p.m. and four heating sections of the barrel (100, 140, 150 and 150°C). The impact of RB inclusion on nutritional profile, starch digestion, physicochemical and textural properties of snack products was evaluated. RB-enriched extrudates showed a lower specific volume and hardness and higher crispness than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 59 publications
(87 reference statements)
3
23
0
Order By: Relevance
“…The total dietary fibre content in the extrudates varied from 1.2% to 2.6% compared to the 0.1% in the control sample, and this amount is directly linked to the legume fortification, the higher the cowpea flour, the higher the total dietary fibre content. The high temperatures used in extrusion can break down the glycosidic bonds in polysaccharides, thus increasing the amount of soluble dietary fibre by converting the insoluble dietary fibre to soluble dietary fibre in extrudates (Renoldi et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total dietary fibre content in the extrudates varied from 1.2% to 2.6% compared to the 0.1% in the control sample, and this amount is directly linked to the legume fortification, the higher the cowpea flour, the higher the total dietary fibre content. The high temperatures used in extrusion can break down the glycosidic bonds in polysaccharides, thus increasing the amount of soluble dietary fibre by converting the insoluble dietary fibre to soluble dietary fibre in extrudates (Renoldi et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As the cowpea flour proportion increased in the formulation, the starch component was replaced and reduced, thereby reducing the continuous phase formed by starch melt. This can result in increased cell coalescence, which in addition to the inclusion of fibre particles causes the rupture of air cells leading to harder extrudates (Renoldi et al ., 2021). Table 4 demonstrates positive correlations between extrudates hardness with protein content ( r = 0.980, P ≤ 0.01) and fibre content ( r = 0.897, P ≤ 0.05) and negative correlation with starch content ( r = −0.945, P ≤ 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…While the inclusion of bran decreased the hardness of extrudates in some studies [ 63 ], most authors reported an increase in hardness [ 64 , 65 , 66 ]. Contrasting results have been obtained for hardness of extrudates enriched with bran compared to those produced with refined flour; this is possibly influenced by processing conditions, as well as the type and amount of included bran.…”
Section: Impact Of Bran On the Characteristics Of Extruded Snack Productsmentioning
confidence: 99%
“…Contrasting results have been obtained for hardness of extrudates enriched with bran compared to those produced with refined flour; this is possibly influenced by processing conditions, as well as the type and amount of included bran. One study on rice bran reported that its inclusion in corn grits-based extrudates (at 10 and 15% w / w ) decreased this index [ 63 ], whereas in studies using wheat (5–15% w / w ) or oat (up to 50% w / w ) bran, hardness increased [ 64 , 65 ]. Differences among the outcomes of various studies can be due to either source of bran or processing conditions.…”
Section: Impact Of Bran On the Characteristics Of Extruded Snack Productsmentioning
confidence: 99%
“…These snacks are derived mainly from cereals and often are not nutritionally balanced. For example, they are high in calories and low in vitamins, minor minerals, dietary fiber, essential amino acids, and other bioactive compounds (Renoldi et al, 2020). The global trend towards a healthier diet is increasingly permeating different levels of society, culture, and education, and expanding across nationalities (Popkin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%